2020
DOI: 10.1002/pat.4872
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ethyl‐bridged diphenylphosphine oxide on flame retardancy and thermal properties of epoxy resin

Abstract: Three commercialized flame retardants, 1,2-bis(diphenylphosphinoyl)ethane (EDPO), 6,6-(1,2-phenethyl)bis-6H-dibenz[c,e][1,2]oxaphosphorin-6,6-dioxide (HTP-6123), and hexa-phenoxy-cyclotriphosphazene (HPCTP), were used to prepare the flame retardant diglycidyl ether of bisphenol A (DGEBA) epoxy resin (EP) under the same experimental conditions. The effects of T g , thermal stability, and water absorption properties of EP caused by the three flame retardants were investigated and compared, together with their fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Scanning electron microscopy (SEM) and digital images of the residues after the cone calorimeter test. The morphology of EP‐0 residue was reported in our previous study 36 [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Scanning electron microscopy (SEM) and digital images of the residues after the cone calorimeter test. The morphology of EP‐0 residue was reported in our previous study 36 [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Resultsmentioning
confidence: 88%
“…Limiting oxygen index (LOI), UL‐94, cone calorimeter tests, thermalgravimetric analysis/infrared (TGIR) spectrometry, microstructure of the char residues, and water absorption were performed as described in our previous work, 28,36 more details are provided in the supporting information.…”
Section: Methodsmentioning
confidence: 99%
“…The average effective heat combustion (av‐EHC), which was usually equal to the ratio of HRR to mass loss rate, corresponded to the combustion degree of volatile gas, of EP/PBO‐1.0 was lower than that of EP, showing the incomplete combustion in gaseous phase. It was mainly attributed to free radicals trapping effect of phosphorus containing groups 27,33,36 . Moreover, av‐COY/av‐CO 2 Y value of EP/PBO‐1.0 raised to a certain extent compared to EP, further suggested that PBO could exert gaseous phase activity.…”
Section: Resultsmentioning
confidence: 94%
“…It was mainly attributed to free radicals trapping effect of phosphorus containing groups. 27,33,36 Moreover, av-COY/av-CO 2 Y value of EP/PBO-1.0 raised to a certain extent compared to EP, further suggested that PBO could exert gaseous phase activity. Based on the above results, EP modified with PBO possessed excellent flame retardancy, lower heat, and smoke release product.…”
Section: Flame Retardancymentioning
confidence: 90%
“…Phosphorus-containing flame retardants have gained increased attention after movements by jurisdictions around the world, such as European Union, to either ban or phase out halogenated flame retardants due to their toxicity and negative impacts on the environment . Among the various organophosphorus flame retardants, diphenyl phosphine oxide (DPO) has been successfully commercialized and used in epoxy resins due to its high flame-retardant efficiency and acceptable price. , Usually, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) is directly added as a flame retardant in prepolymers of epoxy resin, and it was then covalently functionalized into an epoxy resin by reacting with the oxirane ring to form an addition product . However, there are some major drawbacks for DOPO-modified epoxy resins: (1) high dosage of DOPO needed, (2) decreased T g of the cured epoxy polymer, (3) poor humidity resistance property, and (4) decreased thermal decomposing temperature .…”
Section: Introductionmentioning
confidence: 99%